HUBUNGAN KONSUMSI MAKANAN TINGGI INDEKS GLIKEMIK DENGAN KEPARAHAN ACNE VULGARIS PADA SISWA SMAN 10 SAMARINDA: THE RELATIONSHIP BETWEEN THE CONSUMPTION OF HIGH GLYCEMIC INDEX FOODS AND THE SEVERITY OF ACNE VULGARIS IN STUDENTS OF SMAN 10 SAMARINDA - Muhajir, La Ode Muhammad Sakaum; Toruan, Vera Madonna Lumban; Sulistiawati (ITKES Wiyata Husada Samarinda, 2024)
Acne vulgaris is a chronic pilosebaseous gland inflammation with multifactorial causes that manifests in form of comedone, papule, pustule, nodule, and cyst. Several factors that influenced formation and severity of acne vulgaris are genetic, race, hormone, stress, climate, temperature, humidity, cosmetic, medicine, and diet. The purpose of this study is to analyze the relationship of high glycemic index food consumption with acne vulgaris severity in students of SMAN 10 Samarinda. The design of this this study is analytic observational with cross sectional approach. Primary data was taken from students of SMA Negeri 10 Samarinda with mild, moderate, and severe acne vulgaris using purposive sampling technique. Acne vulgaris severity were determined by a dermatologist. Ninety nine respondents’ high glycemic index food consumption data were obtained from daily consumption table for 30 days and Food Frequency Questionnaire (FFQ). Results acquired majority of respondents have high frequency of high glycemic index food consumption (55.6%) and majority of respondents have mild acne vulgaris (53.5%). The statistical analysis used Chi-Square test acquired the value of P=0.300 (P>0.05). It was concluded that there is no significant relationship of high glycemic index food consumption with acne vulgaris severity rate in students of SMA Negeri 10 Samarinda.